2016
DOI: 10.1002/cne.24012
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of intact retinal ganglion cell terminals after axonal transport loss in the DBA/2J mouse model of glaucoma

Abstract: Axonal transport defects are an early pathology occurring within the retinofugal projection of the DBA/2J mouse model of glaucoma. Retinal ganglion cell (RGC) axons and terminals are detectable after transport is affected, yet little is known about the condition of these structures. We examined the ultrastructure of the glaucomatous superior colliculus (SC) using three-dimensional serial block-face scanning electron microscopy (3-D EM) to determine the distribution and morphology of retinal terminals in aged m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 97 publications
5
37
0
Order By: Relevance
“…In our sample of 9m D2 mice, we found that RGC axon terminals were lost in an IOP-dependent manner. We did not see evidence of either RGC axon terminal atrophy or swelling, as has been reported in ultrastructural studies of the SC (Smith et al, 2016). Several possibilities could account for this difference.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In our sample of 9m D2 mice, we found that RGC axon terminals were lost in an IOP-dependent manner. We did not see evidence of either RGC axon terminal atrophy or swelling, as has been reported in ultrastructural studies of the SC (Smith et al, 2016). Several possibilities could account for this difference.…”
Section: Discussionsupporting
confidence: 69%
“…Prior studies have indicated that RGC axon terminals in the superior colliculus (SC) are lost fairly late in disease in DBA/2J and microbead-injected mice and that terminal loss is preceded by swelling followed by atrophy (Crish et al, 2010; Smith et al, 2016). Additionally, we have shown that five weeks of a relatively modest and sustained OHT triggered by anterior chamber microbead injections does not have any effect on RGC axon terminal size or density in the dLGN (Bhandari et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have suggested that RGC axon terminals in the dLGN and superior colliculus persist 418 fairly late into disease in rodent glaucoma models Smith et al, 2016). However, to test 419 whether this reduction in mEPSC frequency might be due to the loss or atrophy of RGC axon terminals, 420…”
mentioning
confidence: 99%